2010
DOI: 10.1111/j.1464-410x.2010.09818.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered transcription factor E3 expression in unclassified adult renal cell carcinoma indicates adverse pathological features and poor outcome

Abstract: RESULTS• Of the 25 cases analyzed, 8 (32%) showed positivity for TFE3 and 17 were negative for TFE3 staining. Two tumors with ASPL-TFE3 gene fusion also showed TFE3 overexpression.• Fifty percent of the positive patients had lymph node metastatic disease, whereas only one TFE3-negative patient (5.8%) showed evidence of lymph node spread and cava thrombus at diagnosis. Of the TFE3-positive patients, three had a vena cava thrombus (37.5%). Seven of the eight positive cases (87.5%) were diagnosed with a high Fuhr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 19 publications
0
24
1
Order By: Relevance
“…In our study, in all patients the diagnosis was made at a younger age (mean 28 years old). Series have reported mean tumor size ranging from 6.8 to 9.2 cm in the largest diameter, which is larger than the 5.8 cm in our series [4,23,25].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In our study, in all patients the diagnosis was made at a younger age (mean 28 years old). Series have reported mean tumor size ranging from 6.8 to 9.2 cm in the largest diameter, which is larger than the 5.8 cm in our series [4,23,25].…”
Section: Discussioncontrasting
confidence: 56%
“…The grading system is determined on nuclear characteristics and has been proven to be a powerful prognostic predictor for RCC [43–45]. One report indicated that in TFE3‐positive RCCs the diagnosis of a high Fuhrman grade (III/IV) was made in 87.5% of cases and the 5‐year cancer‐specific survival rate was low (15.6%) [25]. In our study, six cases (75%) also showed higher Fuhrman grade (III/IV).…”
Section: Discussionmentioning
confidence: 99%
“…In unclassified cases of RCC, adverse clinicopathological parameters are associated with positive expression of transcription factor E3 (TFE3) [3]. Studies have shown that the 5-year cancer-specific survival rate for TFE3-positive patients was 15.6% as compared to 87.5% for TFE3-negative patients [3].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the 5-year cancer-specific survival rate for TFE3-positive patients was 15.6% as compared to 87.5% for TFE3-negative patients [3]. TFE3 positivity in RCC was significantly associated with shorter cancer specific survival ( P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…78-80 (Table 1) In RCC patients, higher TFE3 expression correlates independently with worse patient outcomes. 81,82 …”
Section: Mechanism Of Tfe-fusion Oncogenesis: Dysregulated Protein mentioning
confidence: 99%